Intuition in Information Technology Investment Decision: A Quantitative Method - Kusumawati, Aris; Subriadi, Apol Pribadi (Institut Teknologi Sepuluh Nopember, 2019)
IT investment decisions made by the company have uncertain value characteristics; have a high risk than other capital investment failures and intangible benefits of expected. In this situation, effective decision making is an important (perhaps most important) part of managerial activity. In this article, we analyze the influence of decision making under uncertainty, company size, and environmental hostility to intuition and analyze the intuition of company performance. There are five companies as study sample (ie: university, hospital, regional owned enterprises, creative industry, and software house industry) in East Java, Indonesia. The method used was a survey. The respondents were Top Level Management that is responsible for IT investment decision. Data analysis techniques used was Structural Equation Modeling-Generalize Structure Component Analysis (SEM-GSCA). Although intuition process is critical for effective IT investment decision making, we found that: (1) decision making under uncertainty and environmental hostility did not affect on intuition; (2) company size has a positive effect on intuition, and (3) intuition has a positive effect on company performance